Slowing of EEG Background Activity in Parkinson’s and Alzheimer’s Disease with Early Cognitive Dysfunction - Benz, Nina; Hatz, Florian; Bousleiman, Habib; Ehrensperger, Michael M.; Gschwandtner, Ute; Hardmeier, Martin; Ruegg, Stephan; Schindler, Christian; Zimmermann, Ronan; Monsch, Andreas Urs; Fuhr, Peter (Frontiers in Aging Neuroscience, 2014)
Background: Slowing of the electroencephalogram (EEG) is frequent in Parkinson’s (PD) and Alzheimer’s Disease (AD) and correlates with cognitive decline. As overlap pathology plays a role in the pathogenesis of dementia, it is likely that demented patients in PD show similar physiological alterations as in AD. Objective: To analyze distinctive quantitative EEG characteristics in early cognitive dysfunction in PD and AD. Methods: Forty patients (20 PD- and 20 AD patients with early cognitive impairment) and 20 normal controls (NC) were matched for gender, age and education. Resting state EEG was recorded from 256 electrodes. Relative power spectra, median frequency (4-14Hz) and neuropsychological outcome were compared between groups. Results: Relative theta power in left temporal region and median frequency separated the three groups significantly (p = .002 and p < .001). Relative theta power was increased and median frequency reduced in patients with both diseases compared to NC. Median frequency was higher in AD than in PD and classified groups significantly (p=.02). Conclusions: Increase of theta power in the left temporal region and a reduction of median frequency were associated with presence of AD or PD. PD patients are characterized by a pronounced slowing as compared to AD patients. Therefore in both disorders EEG slowing might be a useful biomarker for beginning cognitive decline.